Analysis of Nutritional Status of Adolescent Male Futsal Players in The U-16 Category on The Futsal Root Team - Hasan Basri; Rayhan Rasyid Zuhdy; Tatang Iskandar; Azi Faiz Ridlo (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Nutrition status is a measure of success in fulfilling nutrition for a person as indicated by body weight and height. Nutritional status is also defined as a health status resulting from a balance between nutritional needs and inputs. The purpose of this study was to determine the adequacy level of nutritional status in a person. The method used in this analysis process is cross sectional, with a total sample of 18 futsal players aged 14-15 years. The sampling process in this study was active players on the Akar Futsal Academy team, and were ready to participate in the research until it was finished. The results of this research data show that the average status is normal by calculating the Body Mass Index, the normal status is in the adequacy of fat and carbohydrates, and the status is deficient in the adequacy of protein and daily calorie consumption. At this conclusion it can be concluded to start paying more attention to the needs of the body's own nutrition as a form of fulfillment of nutrients.